Manajemen Emosi di Masa Pandemi - Bakhoh Jatmiko; Sherly Ester E. Kawengian; Kapoyos Kapoyos (Sekolah Tinggi Theologia Nazarene Indonesia, 2021)
Covid-19 pandemic has shaken the human society in this century. Almost all of life sectors are affected and closely parelized by it. It can be avoided that tis pandemic causes various vital problems including the problem of human’s psychology. Many researches have been conducted found that the level of stress and mental’s problems are raising. Therefore, this reaserch aims to find biblical principels on managing emotion affected by this harsh situation .The authors use quantitative research method with descreptive approach focusing on textual study from Paslm 56. The authors also use various literatures and documents and all supportive data. This reseach found that the emotional problems can be solved by the emotions menaging principles conducted by David also implemented by the Christians. In the experience of wrestling with negative emotion as a response of difficult situations, Christians require to develop oppenes to what they feel, changing the perspective on tha live’s adversity, and develop the positive attitude.